Raising the Status of Women in Matriark from the Perspective of Cheri Register's Feminist Theory: (Pemartabatan Wanita dalam Novel Matriark daripada Perspektif Feminis oleh Cheri Register) (Malay Literature, 2020)
This article is based on the realization that literary works by men often depict stereotypical images of women, while women's experiences are sidelined, women's voices muted and depictions merely highlight and focus on men. The true characteristics of women can only be brought forth by studying texts produced by women writers. Therefore, this study takes a detailed look at Samsiah Mohd. Noor's novel, Matriark (2018), using the five principles of Cheri Register's feminist theory-the text as a forum for women, helping to achieve cultural androgyny, providing role models, promote sisterhood and augment consciousness-raising. Through the application of these principles, it is found that women have their own experiences, voices, desires, visions, and culture. The analysis of the novel Matriark from the perspective of Cheri Register's feminist theory proves that the writer raises the status of women through the depiction of their own experiences, voices, aspirations, ambitions and culture.Keywords: Women writers, women's status, feminist theory